Community Needs for Potential Development Volunteer – Focused Tourism: Case Study of Mon Bang Khadi Community - Chaijan, Khunyarin (Journal of Thai Hospitality and Tourism, 2020)
The development of volunteer tourism management for Bang Kradi community needs is the main target group as a tourism service. This is an important mechanism for promoting and encouraging the Bang Kradi community to be a model for volunteer tourism management. Therefore, a research study of community needs for volunteer tourism management is needed. This is quantitative research using population survey research techniques in the Mon Bang Kradi community, Bang Khun Tien district, Bangkok. The study found that the Mon Bang Kradi community has the highest level of demand for volunteer-based tourism ( = 4.3749). The Songkran festival is the most popular activity for volunteer tourism (17.40%), followed by the traditional merit of the village (13.87%), the merit flower festival (10.97%), and the honey offering ceremony (10.84%).